‘Miracle seeds,’ informational curses? The risk of high expectations for new agricultural technologies - Miehe, Caroline; Nabwire, Leocardia; Sparrow, Robert; Spielman, David J.; Van Campenhout, Bjorn (International Food Policy Research Institute, 2023)
Over the next few decades, farmers in sub-Saharan Africa will need to produce more food on less land and under increasingly difficult climatic conditions. The use of climate-smart agricultural practices and improved technologies such as higher-yielding and drought-tolerant crop varieties are thought to be at least part of the solution. Unfortunately, concerns are rising that the use of improved inputs and technologies across the region now seems to be stagnating—or at least advancing at a slower pace than required.